Social Cognition Deficits: Current Position and Future Directions for Neuropsychological Interventions in Cerebrovascular Disease - Progress Njomboro (Behavioural Neurology)
Neuropsychological assessments of cognitive dysfunction in cerebrovascular illness commonly target basic cognitive functions involving aspects of memory, attention, language, praxis, and number processing. Here, I highlight the clinical importance of often-neglected social cognition functions. These functions recruit a widely distributed neural network, making them vulnerable in most cerebrovascular diseases. Sociocognitive deficits underlie most of the problematic social conduct observed in patients and are associated with more negative clinical outcomes (compared to nonsocial cognitive deficits). In clinical settings, social cognition deficits are normally gleaned from collateral information from caregivers or from indirect inferences made from patients’ performance on standard nonsocial cognitive tests. Information from these sources is however inadequate. I discuss key social cognition functions, focusing initially on deficits in emotion perception and theory of mind, two areas that have gained sizeable attention in neuroscientific research, and then extend the discussion into relatively new, less covered but crucial functions involving empathic behaviour, social awareness, social judgements, and social decision making. These functions are frequently impaired following neurological change. At present, a wide range of psychometrically robust social cognition tests is available, and this review also makes the case for their inclusion in neuropsychological assessments.